The Impact of Perceived Treatment Assignment on Smoking Cessation Outcomes Among African-American Smokers - Thomas, Janet L. (Springer-Verlag, 2008)
BACKGROUND: The double-blind placebo-controlled design is commonly considered the gold standard in research methodology; however, subject expectation bias could subvert blinding. OBJECTIVE: The primary aim of this study was to examine the impact of expectation bias. Specifically, we examined perceived treatment assignment on smoking cessation outcome rates among participants enrolled in a clinical trial of bupropion (150 mg SR, BID). DESIGN: Analyses were conducted on data collected during “Kick It at Swope,” a double-blind, placebo-controlled, randomized trial of 600 African-American smokers. Chi-square and multiple logistic regression analyses were used to examine the impact of perception of assignment on treatment effect and cotinine-verified smoking abstinence rates. PARTICIPANTS: Participants were predominantly middle-aged (mean 44.7, SD 11.2), African-American women (68.6%), who smoked 19 CPD (SD = 8.1). Most had completed at least a high school education or GED (51.6%), and 55% had a monthly family income <$1,800. MEASUREMENTS: At week 6 (end of treatment) and week 26 (end of study), participants were asked to report their perceived treatment group assignment. Self-reported abstinence (weeks 6 and 26) was confirmed using CO and cotinine biochemical verification. RESULTS: After adjusting for actual treatment assignment, age and baseline cotinine, participants who perceived being assigned to bupropion vs. placebo were more likely to be abstinent at weeks 6 (OR = 2.07, 95% CI: 1.29 to 3.33, p = 0.002) and 26 (OR = 1.85, 95% CI: 1.05 to 3.24, p = 0.032). CONCLUSIONS: Results support previous research that expectation bias associated with judgment of treatment assignment is a strong predictor of outcome and confirms this relationship in a smoking cessation trial using bupropion SR among African-American smokers.